Assessing likelihood of using the Bruininks-Oseretsky test of motor proficiency to predict preclinical performance of dental students - Ammar Musawi; Travis Barrett; Hamid Nurrohman; Shalini Bhatia; Kneka Smith (Wiley, 2019)
Abstract Objective The acquisition of motor skills is a key competency for the practice of dentistry, and innate abilities have been shown to influence motor performance. Thus, finding the most efficient manual dexterity tests may predict performance of dental students. The current study used the Bruininks-Oseretsky Test of Motor Proficiency, to assess motor skills of first year (D1) and second year (D2) dental students. Materials and methods Three fine motor subsets of the BOT‐2-fine motor precision, fine motor integration, and manual dexterity-were administered to D1 and D2 dental students in 2017 and 2018. The BOT‐2 subset scores of D1 students were compared with those of D2 students, who had preclinical dental experiences. For D2 students, we tested for correlations between BOT‐2 subset scores and performance scores in a preclinical operative dentistry course. Results No differences were found between D1 and D2 students for any BOT‐2 subtest scores (all Ps > .09). No correlations were found between total scores of each BOT‐2 subtest and the operative dentistry course for D2 students (all Ps > .20). Conclusions Our results suggested the BOT‐2 was not predictive of manual skills of dental applicants or preclinical dental students. Although we assumed students would perform well with instruction, practice, and feedback, we were unable to determine whether innate abilities influenced acquisition of manual dexterity skills. More research about the acquisition of technical clinical skills in dentistry is required.